2019
DOI: 10.3389/fpsyg.2018.02298
|View full text |Cite
|
Sign up to set email alerts
|

Item-Score Reliability as a Selection Tool in Test Construction

Abstract: This study investigates the usefulness of item-score reliability as a criterion for item selection in test construction. Methods MS, λ6, and CA were investigated as item-assessment methods in item selection and compared to the corrected item-total correlation, which was used as a benchmark. An ideal ordering to add items to the test (bottom-up procedure) or omit items from the test (top-down procedure) was defined based on the population test-score reliability. The orderings the four item-assessment methods pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 32 publications
2
86
0
2
Order By: Relevance
“…The method of reliability test was to calculate the corrected item–total correlation (CITC) of each measurement item ( Zijlmans et al, 2019 ). At the same time, the Cronbach’s alpha coefficient, which was the most widely used method for estimating internal consistency reliability ( Trizano-Hermosilla and Alvarado, 2016 ), was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The method of reliability test was to calculate the corrected item–total correlation (CITC) of each measurement item ( Zijlmans et al, 2019 ). At the same time, the Cronbach’s alpha coefficient, which was the most widely used method for estimating internal consistency reliability ( Trizano-Hermosilla and Alvarado, 2016 ), was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…One important aspect in instrument development is achieving a good balance between a small number of items (lengthy questionnaires can induce lower response rates [60]) and adequate reliability. A recent study by Zijlmans, Tijmstra [61] showed that the CITC [62] performed better than other methods at identifying which items can be removed while maximizing reliability. Therefore, items with the lowest CITC should be the first to be considered for removal.…”
Section: Discussionmentioning
confidence: 99%
“…A reliability test was conducted by calculating the CITC of each measurement item. If the value was less than 0.5 (Zijlmans et al, 2019), the index was deleted. Meanwhile, Cronbach's alpha coefficient was calculated.…”
Section: Scale Reliability and Validity Testmentioning
confidence: 99%
“…It is usually evaluated between 0 and 1. If the alpha coefficient is ≥0.7 (Zijlmans et al, 2019), the reliability of the indexes is acceptable. The CITC minimum value of entrepreneurial education teachers' competency scale was 0.692, Cronbach's alpha was 0.952, and the Cronbach's alpha coefficient value after deleting all the observed variables in the table was smaller than the original scale's alpha value, indicating that the scale had high reliability.…”
Section: Scale Reliability and Validity Testmentioning
confidence: 99%